Habitat Characteristics of Small-clawed Otter (Aonyx cinereus) in Ujong Nga, Samatiga,West Aceh - Abdullah Abdullah; M Ali S; Hansri Ar Rasyid (Universitas Syiah Kuala, 2015)
Small-clawed otter (Aonyx cinereus) is the smallest among the sub-family Lutrinae, today occurs population decrease of small-clawed otter caused by human activity, depletion of prey species, and exploitation. This research is done to learn physically and biologically of the habitat characteristic of small-clawed otter. Retrieval of data was held on 1-14 in April 2014. The parameters which used are the amount of tracks found in habitat that is used by the small-clawed otter in Ujong Nga village. The data is collected on small-clawed otter habitat in Ujong Nga and sample used are plot with measure of 30x30m and then divided into 8 plots. The result showed that the small-clawed otter selecting habitat unit with criteria (a) the type of habitat are field, swamp, thatch forest, and riverside; (b) the availabilty of many feed (1,33 tracks per plot), rare (0,33 tracks per plot), less (0,17 tracks per plot); (c) the tracks distance to the nest 0-25 m (1,66 tracks per plot), 25-50 m (1 tracks per plot), 50 m (0,5 tracks per plot); (d) the tracks distance to water source 0-25 m (2,16 tracks per plot), 25-50 m (0,5 tracks per plot), and for distance to 50 m track is not found; and(e) the tracks distance to toilet site0-25 m (1,16 tracks per plot), 25-50 m (0,5 tracks per plot), and 50 m (0,17 tracks per plot). The conclusion of this research habitat characteristic ofAonyx cinereusare fieldwithavailability of many feed, close to water source, clost to nest, and close to toilet site.